TEENAGERS USING CREDIT CARDS BEFORE EMPLOYMENT: FINANCIAL RESPONSIBILITY, PARENTAL ROLE, AND DEBT RISKS - Shahnoza Abdijabborova (The latest news and research in education, 2025)
In today's consumer-driven natural world, teens are increasingly obtaining credit cards, often before securing permanent jobs. This early exposure to credit can have serious consequences for their financial responsibility, parental guidance, and the risks linked with debt accumulation. Understanding these dynamics is critical, especially as financial literacy becomes a necessary skill for navigating adulthood. The purpose of this study is to investigate credit card usage patterns among teenagers, assess their financial responsibility, measure the impact of parental engagement, and determine the associated debt risks.